Recent developments in stainless steels - Lo, K.H.; Shek, C.H.; Lai, J.K.L. (Materials science & engineering. R, Reports : a review journal, 2009)
This article presents an overview of the developments in stainless steels made since the 1990s. Some of the new applications that involve the use of stainless steel are also introduced. A brief introduction to the various classes of stainless steels, their precipitate phases and the status quo of their production around the globe is given first. The advances in a variety of subject areas that have been made recently will then be presented. These recent advances include (1) new findings on the various precipitate phases (the new J phase, new orientation relationships, new phase diagram for the Fe–Cr system, etc.); (2) new suggestions for the prevention/mitigation of the different problems and new methods for their detection/measurement and (3) new techniques for surface/bulk property enhancement (such as laser shot peening, grain boundary engineering and grain refinement). Recent developments in topics like phase prediction, stacking fault energy, superplasticity, metadynamic recrystallisation and the calculation of mechanical properties are introduced, too. In the end of this article, several new applications that involve the use of stainless steels are presented. Some of these are the use of austenitic stainless steels for signature authentication (magnetic recording), the utilisation of the cryogenic magnetic transition of the sigma phase for hot spot detection (the Sigmaplugs), the new Pt-enhanced radiopaque stainless steel (PERSS) coronary stents and stainless steel stents that may be used for magnetic drug targeting. Besides recent developments in conventional stainless steels, those in the high-nitrogen, low-Ni (or Ni-free) varieties are also introduced. These recent developments include new methods for attaining very high nitrogen contents, new guidelines for alloy design, the merits/demerits associated with high nitrogen contents, etc.